(untitled) (Sustainability in Debate, 2013)
The objective of this article is to reflect about the indigenous people who live in the São Francisco river area and how they act in defense of its preservation. In a time that agribusiness is becoming stronger and dams and the canal to divert that river are in construction, many social and environmental conflicts have arisen in that region. The Environment Impact Studies do not take in account the dynamic of those indigenous peoples with their land and how they relate to the São Francisco river. Based on bibliographical research about the conflicts that come with those projects, we conclude that those projects repeat the mistakes from the past in its relation with those indigenous people.